Subclinical Reactivation of Cytomegalovirus Drives CD4+CD28null T-Cell Expansion and Impaired Immune Response to Pneumococcal Vaccination in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. (9th August 2018) - Chanouzas, Dimitrios; Sagmeister, Michael; Faustini, Sian; Nightingale, Peter; Richter, Alex; Ferro, Charles J; Morgan, Matthew David; Moss, Paul; Harper, Lorraine
Abstract : Infection is a leading cause of death in antineutrophil cytoplasmic antibody–associated vasculitis. Here we show that suppression of subclinical reactivation of cytomegalovirus limits CD4 + CD28 null T-cell expansion and that this is associated with improved immune response to a T-cell–dependent pneumococcal vaccine challenge. Abstract: Background: Infection is the leading cause of death in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Expansion of CD4 + CD28 null T cells is associated with increased risk of infection and mortality, but is only present in cytomegalovirus (CMV)–seropositive individuals. We hypothesized that subclinical CMV reactivation drives CD4 + CD28 null T-cell expansion, that this is associated with impaired immune response to heterologous antigens, and that antiviral therapy may ameliorate this. Methods: In a proof-of-concept open-label clinical trial, 38 CMV-seropositive AAV patients were randomized to receive valacyclovir for 6 months or no intervention. CMV reactivation was measured monthly in plasma and urine. CD4 + CD28 null T cells were enumerated at baseline and at 6 months. At 6 months, 36 patients were vaccinated with a 13-valent pneumococcal vaccine. Serotype-specific immunoglobulin G was assayed before and 4 weeks postvaccination to calculate the antibody response ratio. Results: Valacyclovir treatment suppressed subclinical CMV reactivation and reduced CD4 + CD28 null T-cell proportion. CD4 + CD28 null T-cell reduction correlated with improved vaccine response, whereas CMV reactivation associated with reduced response to vaccination. Furthermore, expansion of CD4 + CD28 null T cells was associated with a reduction in the functional capacity of the CD4 compartment. Conclusions: Suppression of CMV may improve the immune response to a T-cell–dependent pneumococcal vaccination in patients with AAV, thus offering potential clinical benefit. Clinical Trials Registration: NCT01633476.